Ownership Concentration and CSR Policy of European Multinational Enterprises - Dam, Lammertjan 1977-; Scholtens, Bert (2013)
This study investigates how ownership concentration in European multinational firms is associated with these firms’ corporate social responsibility (CSR). We employ factor analysis on responsibility data from EIRiS and use a regression analysis. Using firm-level data for almost 700 European firms, we find that shareholder concentration is significantly related to such policies. That is, more concentrated ownership goes hand in hand with poorer CSR policies. In our analysis, we control for size, leverage, profitability, industry, and country of origin. We use several indicators for ownership concentration. We also find that with more concentrated ownership, CSR of the firm gets worse. We suggest that especially with large shareholders, CSR would need to be included in their performance assessment.
Keywords: Multinational enterprises; Europe; Corporate Social Responsibility; Concentrated ownership; Blockholders